Utilization and avoidance of sexual health services and providers by YMSM and transgender youth assigned male at birth in Chicago. Issue 10 (3rd October 2019) - Phillips, Gregory; Neray, Balint; Janulis, Patrick; Felt, Dylan; Mustanski, Brian; Birkett, Michelle
ABSTRACT: Young men who have sex with men (YMSM) and transgender youth assigned male at birth (AMAB) bear a disproportionate burden of the HIV epidemic, yet are sub optimally engaged by sexual health service providers and HIV prevention services. To increase sexual health and HIV prevention behaviors and address disparities in HIV incidence and outcomes among YMSM and AMAB transgender youth, it is critical to understand patterns of service utilization and avoidance. This study examined how and why YMSM and AMAB transgender youth use or avoid sexual health services and service providers in a large Midwestern city within a survey administered to 890 participants from a longitudinal cohort study (RADAR). Results demonstrate low overall use of sexual health services and minimal interest in seeking pre-exposure prophylaxis (PrEP), consistent with prior research. Low awareness of available services was associated with how and where YMSM and trans youth AMAB seek care, with 76% of our sample reporting this as their primary reason for not seeking specific sexual health services. Additional associations are discussed, and recommendations are made for how to improve available services and access.